Using three-dimensional geometric morphometry for facial analysis in patients with the oculo-auriculo-vertebral spectrum - Poláčková, Petra; Borovec, Jiří; Vašáková, Jana; Patzelt, Matěj; Urbanová, Wanda; Mihulová, Michaela; Macek, Milan; Havlovicová, Markéta; Moslerová, Veronika (Orthodontics & craniofacial research, 2024)
AIM: To utilize three-dimensional (3D) geometric morphometry for visualization of the level of facial asymmetry in patients with the oculo-auriculo-vertebral spectrum (OAVS). MATERIALS AND METHODS: Three-dimensional facial scans of 25 Czech patients with OAVS were processed. The patients were divided into subgroups according to Pruzansky classification. For 13 of them, second 3D facial scans were obtained. The 3D facial scans were processed using geometric morphometry. Soft tissue facial asymmetry in the sagittal plane and its changes in two time spots were visualized using colour-coded maps with a thermometre-like scale. RESULTS: Individual facial asymmetry was visualized in all patients as well as the mean facial asymmetry for every Pruzansky subgroup. The mean colour-coded maps of type I and type IIA subgroups showed no differences in facial asymmetry, more pronounced asymmetry in the middle and the lower facial third was found between type IIA and type IIB (maximum 1.5 mm) and between type IIB and type III (maximum 2 mm). The degree of intensity facial asymmetry in affected middle and lower facial thirds did not change distinctly during the two time spots in all subgroups. CONCLUSIONS: The 3D geometric morphometry in OAVS patients could be a useful tool for objective facial asymmetry assessment in patients with OAVS. The calculated colour-coded maps are illustrative and useful for clinical evaluation.
Keywords: Facial Asymmetry; Face; Female; dítě; Cephalometry; zobrazování trojrozměrné; Imaging, Three-Dimensional; ženské pohlaví; Adolescent; lidé; oculo‐auriculo‐vertebral spectrum; facial soft tissue asymmetry; obličej; kefalometrie; Male; three‐dimensional scanning; Goldenhar Syndrome; geometric morphometry; Goldenharův syndrom; Child; mužské pohlaví; asymetrie obličeje; mladiství; Humans